PENGARUH PIJAT PERINEUM SELAMA MASA KEHAMILAN TERHADAP KEJADIAN RUPTURA PERINEUM SPONTAN DI PMB SHINTA NUR ROCHMAYANTI, SSiT., M.Kes - Shinta Nur Rochmayanti; Kholifatul Ummah (Universitas Islam Lamongan, 2018)
Some of the factors that cause perineal rupture consist of maternal factors, fetal factors, and helper factors. A method of reduce perineal rupture is a perinel massage to promote heatlh, blood flow and elasticity of the perineum. Based on preliminary study at PMB Shinta Nur Rochmayanti, SSiT., M.Kes from June to September of 2017 there were 20 births per month, and 70% had spontaneous birthrate while 30% had no perineal rupture. The purpose of this study was to determine the effect of perineal massage during pregnancy on the incidence of Rupture Perineum during delivery at the Midwives Practice Midwife Shinta Nur Rochmayanti, SSiT., M.Kes year 2018. The objektive of this study was to determine the effect of perineal massage on the incidence of perineal rupture in pregnant period during childbirth in independent practice of midwifery in PMB Shinta Nur Rochmayanti, SSiT., M.Kes year 2018.This study is Quasi Experimental study with Post Test Only Control Group Design method. The study was conducted in midwife Mandiri Practice (PMB) Shinta Nur Rochmayanti, SSiT., M.Kes Surabaya in 2018 with subject of 28 pregnant women 36 weeks pregnancy consisting of 14 intervention group and 14 control group. The study was conducted from December 2017 until April 2018, then the data were analyzed by Chi Square test. The incidence of Rupture Perineum in the intervention group after perineal massage was only 14,3% while in the control group 64,3%. The results showed that there was an effect of perineal massage during pregnancy on the incidence of perineum rupture (p <0.05). This study concluded that perineal massage during pregnancy affects the incidence of perineal rupture at delivery.Keywords: perineal massage, pregnant periode, perineal rupture